2013
DOI: 10.1080/02664763.2012.755320
|View full text |Cite
|
Sign up to set email alerts
|

To tell or not to tell: Negotiating disclosure for people living with HIV on antiretroviral treatment in a South African setting

Abstract: Disclosure of HIV status occurs for a variety of reasons and in various contexts, such as to sexual partners to enable safer sexual choices, to health-care workers to access treatment and care services and to family and community members to gain various forms of support. The reasons for disclosure or non-disclosure are shaped by the relationships, needs and circumstances of people living with HIV (PLHIV) at the time of disclosure. The purpose of this study was to investigate and describe the act and experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…This expectation is not feasible for many men and women living with HIV infection. Our findings suggest a need for approaches with attention to gender and relationship dynamics, with particular attention to the fear, mistrust, and misunderstandings of serodiscordance surrounding disclosure (1113, 18, 20, 25, 36). …”
Section: Discussionmentioning
confidence: 91%
“…This expectation is not feasible for many men and women living with HIV infection. Our findings suggest a need for approaches with attention to gender and relationship dynamics, with particular attention to the fear, mistrust, and misunderstandings of serodiscordance surrounding disclosure (1113, 18, 20, 25, 36). …”
Section: Discussionmentioning
confidence: 91%
“…Stigma and discrimination has also been found associated with a decreased willingness to disclose one’s HIV status, which in turn may lead to depression and anxiety (2, 2427). Stigma and discrimination in health care settings lead to PLWH hiding their HIV status from providers (8, 27, 28), creating a primary barrier to HIV testing (7, 12, 29, 30) and care-seeking (7, 10, 31). A meta-analysis of global studies published between 1996 and 2013 found that people who had experienced HIV-related stigma were at greater risk of depression, lower social support, and “were 21% less likely to access or use health and social services” (32).…”
Section: Introductionmentioning
confidence: 99%
“…[5]. K65R was evaluated by OLA in 2014 and pyrosequencing was performed on enrollment plasma from those with subsequent virologic treatment failure in 2006 [4].…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Pathways linking ART initiation to repercussion on various social dimensions are complex and partially understood. ART initiation is associated with HIV status disclosure to relatives [4][5][6], which in turn not only lead to increased social support, but also to rejection [7,8]. Similarly, the impact of ARTon stigma and discrimination seems ambiguous [9][10][11].…”
mentioning
confidence: 98%